Azole Susceptibility and Transcriptome Profiling in Candida albicans Mitochondrial Electron Transport Chain Complex I Mutants - Sun, Nuo (American Society for Microbiology, 2013)
Mitochondrial dysfunction in pathogenic fungi or model yeast causes altered susceptibilities to antifungal drugs. Here we have characterized the role of mitochondrial complex I (CI) of Candida albicans in antifungal susceptibility. Inhibitors of CI to CV, except for CII, increased the susceptibility of both patient and lab isolates, even those with a resistance phenotype. In addition, in a C. albicans library of 12 CI null mutants, 10 displayed hypersusceptibility to fluconazole and were severely growth inhibited on glycerol, implying a role for each gene in cell respiration. We chose two other hypersusceptible null mutants of C. albicans, the goa1Δ and ndh51Δ mutants, for transcriptional profiling by RNA-Seq. Goa1p is required for CI activity, while Ndh51p is a CI subunit. RNA-Seq revealed that both the ndh51Δ mutant and especially the goa1Δ mutant had significant downregulation of transporter genes, including CDR1 and CDR2, which encode efflux proteins. In the goa1Δ mutant, we noted the downregulation of genes required for the biogenesis and replication of peroxisomes, as well as metabolic pathways assigned to peroxisomes such as β-oxidation of fatty acids, glyoxylate bypass, and acetyl coenzyme A (acetyl-CoA) transferases that are known to shuttle acetyl-CoA between peroxisomes and mitochondria. The transcriptome profile of the ndh51Δ mutant did not include downregulation of peroxisome genes but had, instead, extensive downregulation of the ergosterol synthesis gene family. Our data establish that cell energy is required for azole susceptibility and that downregulation of efflux genes may be an outcome of that dysfunction. However, there are mutant-specific changes that may also increase the susceptibility of both of these C. albicans mutants to azoles.